Working models of attachment and health threats: Distress, appraisal, coping and health-related behaviours in colorectal cancer. - Gayton, Jane E. (University of Ottawa (Canada), 2001)
Attachment theory has evolved from early work on infant-caregiver relationships to exploring the role of attachment processes in close relationships in adults. Most recently, it has been investigated under conditions of threat or stress. Bowlby (1973, 1988) proposed that attachment processes should be most activated under these circumstances. Using a cross-sectional design, the present project investigated working models of attachment within the context of a threat to health. Specifically, it tested components of a model proposed by Collins and Read (1994) that attachment models affect relevant behavioural outcomes via cognitive and emotional responses. Working models of attachment, emotional distress, appraisal and coping were studied in 71 male and female colorectal cancer patients undergoing adjuvant treatment. Health-related behaviours were chosen as behavioural outcomes. Although measurement and design issues did not permit a complete test of the model, the results suggested that working models of attachment are related to distress and coping in ways that are consistent with attachment theory. Perceived threat of illness was related to negative self models. Emotional distress was found to be primarily a function of model of self and mediated the relationship between the self model and coping. Model of self also had a direct link with the degree to which patients engaged in healthful behaviours. Results for model of other were less robust. Results of this study suggest that internal working models of attachment are important constructs in situations beyond close relationships.
Keywords: Psychology, Clinical.